코로나19와 한국의 글로벌가치사슬(GVC) 변화 - 구양미; Yangmi Koo (한국경제지리학회지, 2020)
본 연구의 목적은 코로나19의 확산에 따른 한국의 무역 및 산업의 변화를 글로벌가치사슬 관점에서 분석하고 시사점을 제시하는 것이다. 이를 위해 코로나19와 직접적으로 관련 있는 방역용품과 GVC 참여도가 높은 IT산업을 분석하였다. 방역용품은 코로나19의 확산에 따라 수출입 변동 폭이 컸다. 마스크의 경우 최종재는 수출입이 급격히 변화했지만 중간재의 변화는 상대적으로 크지 않았다. 한국의 IT산업은 GVC에서 전방참여도가 높아지고 후방참여도가 낮아지는 전반적인 변화 속에서 주요 무역대상국별로 차별화된 특성을 보였다. 아직까지 코로나19로 인한 변화가 직접적으로 나타나지는 않았지만, 중국, 베트남과의 생산 연계와 무역 의존도가 높은 상황에서 다변화 전략의 필요성이 높아졌다. 코로나19는 여전히 진행 중으로 포스트 코로나 시대의 GVC 변화에 대응하기 위한 기업의 전략과 정책적 노력이 필요하다. The purpose of this study is to analyze the changes in trade and industry of Korea and suggest implications from the perspective of global value chains following the spread of COVID-19. To this end, products for prevention of epidemics which is directly related to COVID-19 and IT industries with high GVC participation were analyzed. Due to the spread of COVID-19, the variation in import and export of products for prevention of epidemics was large. In the case of masks, import and export of final goods changed drastically, but the change in intermediate goods was not significant relatively. Korea’s IT industry has been differentiated according to major trading partners amid overall changes in GVCs which is summarized as higher forward participation and lower backward participation. While no particular change resulted from COVID-19 has yet been made directly, the need for diversification strategies should be taken into account at a time when the production links with China and Vietnam are close and the dependence on trade with these countries is high. The COVID-19 is still in progress, requiring corporate strategies and policy efforts to respond to changes in GVCs in the post-COVID-19 era.